212k views
2 votes
1/6x - 1/3 = 5/4x + 3/4

User Alb Bolush
by
4.7k points

2 Answers

1 vote

Answer:

Explanation

1/6x - 5/4x = 1/3 + 3/4

0.16x - 1.25x = 0.3 + 0.75

-1.09x = 1.05

x = 1.05/-1.09

x = 0.96

User Kishore Tamire
by
5.0k points
3 votes
The answer is x=-1.


•Multiply both sides by the Least Common Denominator:
2-4x=15+9x
•Subtract 2 from both sides:
-4x=15+9x−2
•Simplify 15+9x−2 to 9x+13:
-4x=9x+13
•Subtract 9x from both sides:
-13x=13
•Divide both sides by -13 and get your answer, x=-1.

Hope this helped!!
User Kyle Campos
by
4.7k points